Exploring changes in family routines and family quality of life among Israeli families during the COVID-19 pandemic - Liat Hen-Herbst; Yael Fogel (PeerJ, 2025)
Background The COVID-19 pandemic has significantly disrupted family life globally, altering daily routines and impacting family quality of life (FQOL). This study explores the changes in family routines during the pandemic lockdowns and their correlation with FQOL. Methods Participants included 253 families with children aged 3 to 18, recruited through an online survey. Families completed the Family Routines Inventory and the FQOL Scale, reporting on both pre-pandemic and during-pandemic conditions. Data analysis included principal component analysis and regression analysis to identify changes in routine frequency and importance and their predictive relationship with FQOL. Results The principal component analysis resulted in three distinct factors of family routines, highlighting significant shifts in the frequency and importance of these routines from before and during COVID-19. Notably, routines involving within-family interactions increased, whereas those involving external interactions decreased. Regression analysis showed that the frequency of within-family interactions (Factor 1) and the importance of general morning and evening routines (Factor 3) significantly predicted FQOL, accounting for 24% of the variance in FQOL scores during the pandemic. Conclusion The COVID-19 pandemic has underscored the critical role of family routines in maintaining FQOL in times of crisis. Interventions aimed at supporting families should consider enhancing the adaptability and resilience of family routines to foster well-being during unpredictable stressors. Future research should continue to explore the dynamics of family routines and their impact on FQOL across different types of crises.